Optimisation of cholesterol reduction in prawn by ‘Limau madu’ (citrus reticulata blanco) fruit extract using response surface methodlogy / Nordiana Kamarudin - Kamarudin, Nordiana (2008)
The purpose of this study was to investigate the usage of ‘Limau madu’ fruit extract on the reduction of cholesterol in prawn. ‘Limau madu’ fruit extract was diluted in the range of 100 to 14 %. By using Response Surface Methodology (RSM) of the MINITAB software version 14, experimental design could be created whereby test variables such as ‘Limau madu’ fruit extract concentration; temperature and time of immersion were used. Prawn was immersed in different ‘Limau madu’ extract concentrations and shaken in shaking water bath with temperature range from 32 to 45 0C, for immersion times ranging from 7 to 23 minutes. The treated prawns were analyses their cholesterol content using AOAC 994.10 method. The optimum reduction of cholesterol could be predicted and the reduction was 79.10% when the prawn was treated with ‘Limau madu’ fruit extract at the feasible optimum condition of 29 % ‘Limau madu’ fruit extract concentration, 280C of immersion temperature and 43 minutes of immersion time. Besides, the significant regression equation or model at the 5% level was created for the reduction of cholesterol in the prawn treated by ‘Limau madu’ fruit extract. It was also found that the reduction of cholesterol value of the optimum condition could be accepted because the difference values between the percentage reduction of cholesterol predicted by RSM of MINITAB software version 14 (79.12%) and verification experiment (84%) was not significantly different at the 5% level.